2015
DOI: 10.1007/s40258-015-0190-5
|View full text |Cite
|
Sign up to set email alerts
|

Vision Amniotic Leak Detector (ALD) to Eliminate Amniotic Fluid Leakage as a Cause of Vaginal Wetness in Pregnancy: A NICE Medical Technology Guidance

Abstract: In prelabour rupture of membranes (PROM) or preterm PROM the amniotic membranes rupture prior to labour. Where this is not overt a speculum examination is undertaken to confirm diagnosis. The Vision Amniotic Leak Detector (ALD) is a panty liner that can diagnose amniotic fluid as a cause of vaginal wetness. It was evaluated by the UK National Institute for Health and Care Excellence (NICE) as part of the Medical Technologies Evaluation Programme. The sponsor (CommonSense Ltd) identified five studies, of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Such reagent pads have been recommended as a means of reducing more invasive methods such as speculum examination (Ray et al, 2015) that women may find embarrassing, stressful and painful (Seehusen et al, 2006). However, women's views of the use of reagent pads do not appear to have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such reagent pads have been recommended as a means of reducing more invasive methods such as speculum examination (Ray et al, 2015) that women may find embarrassing, stressful and painful (Seehusen et al, 2006). However, women's views of the use of reagent pads do not appear to have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a reagent pad to confirm rupture of membranes has been tested among a group of women reported as being mainly at high obstetric risk (Mulhair et al, 2009). Such reagent pads have been recommended as a means of reducing more invasive methods such as speculum examination (Ray et al, 2015) that women may find embarrassing, stressful and painful (Seehusen et al, 2006). However, women's views of the use of reagent pads do not appear to have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that M. hominis infection is associated with premature birth, malformation, and even death of the fetus, resulting in seriously adverse consequences for pregnant women and babies (Michou et al, 2014;Kersin et al, 2020;Ansari et al, 2021;Paira et al, 2021). Hence, the early detection of the infection may reduce maternal and neonatal morbidity (Ray et al, 2015).…”
Section: Introductionmentioning
confidence: 99%